Alfred Nobel : the man behind the Peace Prize - Wargin, Kathy-jo.; Pullen, Zachary (Chelsea, Mich. : Sleeping Bear Press, 2009)
"Alfred Nobel was the man who founded what became known as The Nobel Prizes. Nobel also invented dynamite, becoming very wealthy from his invention. Saddened by its use for harmful destruction, Nobel left his fortune to create yearly prizes for those who have rendered the greatest services to mankind"--Provided by publisher.
Keywords: Nobel, Alfred Bernhard, -- 1833-1896 -- Juvenile literature; Nobel, Alfred Bernhard, -- 1833-1896.; Chemical engineers -- Biography -- Juvenile literature .; Dynamite -- Juvenile literature; Nobel Prizes -- Juvenile literature; Chemical engineers -- Biography; Dynamite; Nobel Prizes